Sistem Informasi Smart Security untuk Perumahan dengan QR Code Berbasis Web - Asep Deden Rahmat S (Unversitas Muhammadiyah Riau, 2022)
This information system aims to make it easier for security officers to record residents who enter or leave the housing. This information system helps the housing admin get data on residents who enter and leave housing. There is no data collection system available for residents who will enter or leave the Graha Bakti Persada housing area. The unavailability of a support system that can be used as an effort to prevent crime. Building a Smart Security Information System with a web-based QR Code. Create a system that makes it easier for security officers. see the QR Code results based on the appropriate citizen ID in the database. The research methodology is to analyze the problems that occur, and design procedures. Suggestions that can be used as a reference for further system developers are the need to improve functions and menus in the application.